Suwerenność państwa w stosunkach międzynarodowych w doktrynie Roberta Bellarmina - Wielomski, Adam (Societas et Ius, 2018)
Respublica Christiana (also referred to as Christianitas) is a Pan-European religiopolitical project of the medieval Europe, having claims for universal power upon the whole world being converted into the faith in the resurrection of Jesus Christ. That is a great medieval dream about the theologicopolitical unity about which Jan Baszkiewicz once wrote that it has never materialized. This opinion we do not side with and we hold on to the position that the dream did indeed materialize – even if for a moment – during the pontificate of Innocent III in 1214-16 when, upon the French defeating the emperor Otto IV at the battle of Bouvenies, what was genuinely united in the pontifical hands were the highest religious and political powers.